Antara Hukum Murtad dalam Islam dengan Kebebasan Beragama dalam Hak Asasi Manusia (HAM) - Syamsuddin Syamsuddin (Institut Agama Islam Negeri Palangka Raya, 2021)
This article describes the law of apostasy in Muslim scholars' ijtihad and freedom of religion in terms of human rights. This research uses normative legal research methods. The research aims to describe and clarify the views of ulama on the law of apostasy and to dialogue with religious freedom as regulated in human rights. This research concludes that the majority of scholars consider apostasy as a criminal offense which is punishable by absolute death after refusing to revert to Islam. Few modernist liberals think that the death penalty is imposed only when there is hostility or rebellion committed when leaving Islam. As for universal human rights, it recognizes freedom of religion as well as freedom to change religions. This freedom is limited only to the freedoms of other people and other general freedoms. Religious freedom in Indonesia applies in a limited way by providing guarantees to embrace a religion, limiting freedom of religion in recognized religions, and protecting religion from blasphemy. Islam frees anyone to embrace a certain religion, but those who have chosen Islam are bound by the core values of hifz al-din (maintaining religion) so that apostasy is a criminal act.